The Al-Hakim saying in Mustadrak: “on the condition of the two sheikhs or one of them” - Bakhsh, Abeer Adnan Khuda (Journal of Islamic Sciences, 2019)
The problem of the research lies in the difference of scholars on Murad al-Hakim in his saying: “On the condition of the two sheikhs or one of them.” Thus, the research aimed to study the attribution of (8) hadiths from Al-Mustadrak to Al-Saheehain, a critical and applied study, in order to reach the extent of the degree of the hadith and its men with al-Hakim statement on The condition of the two sheikhs or one of them, and the statement of the scholars ’statements on the degree and validity of the hadith, if any, and its compatibility with the ruling of al-Hakim, and reaching a final ruling on the degree of the hadith. The researcher followed the deductive, applied, critical approach by graduating the hadith, then translating the narrators from the books of wound and modification, mentioning the rulings of critics - ancient and contemporary - to the hadith as a basis and reflection, and mentioned the provisions of Al-Dhahabi and then discussing al-Hakim, and ended with the researcher’s weighting, according to the rules of the speakers. The research is from an introduction. The prelude to the definition of al-Hakim and his book, and two chapters; the first dealt with the conditions of the two sheikhs in their books and al-Hakim wanted al-Hakim them in three sections, while the second included: the practical study of the number of (8) hadiths, which al-Hakim judged them to be on the condition of the two sheikhs or one of them, according to the one who is being held, in addition to Conclusion and indexes .. The results of the research showed that Murad al-Hakim said: “On the condition of the two sheikhs, or one of them,” in the course of it, it is divided into sections. The first of which are the hadiths that al-Hakim brought out with the foundations of Hajj Bukhari and Muslim with their narratives in their correct, or one of them, and here al-Hakim says about him: (Al-Bukhari or Muslim) “It is correct, and there is a second section. Hadiths that al-Hakim passes and ruled on health on the condition of the two sheikhs or one of them, while some of its narrators did not come out to them by the two sheikhs and neither of them protested, but rather they gave them to them - in evidence, follow-up and suspensions, so al-Hakim made a mistake in His ruling on these hadiths, and a third section; al-Hakim produces and corrects hadiths, and for Be not on the condition of the two sheikhs, nor one of them, then it becomes clear that the hadith is authentic according to what al-Hakim said - may God have mercy on him. According to the results, the researcher recommended that there is no absolute confidence in the hadith, as soon as al-Hakim is corrected, although most of what is correct is correct. Evil ... etc.).